THE IMPLEMENTATION OF THEMATIC LEARNING IN EARLY CLASS OF ELEMENTARY SCHOOL (Universitas Negeri Semarang, 2017)
The purpose of this research is to described implementation and obstacles thematic learning on early class in prymary school. The research was descriptive qualitative which subject research were 6 head masters and 18 teachers of six primary school.Technique data collection used is observation, interview, documentation, and field notes. Technique data analysis used analysis before in the field, analysis for in the field (data reduction, presentation of data, and conclusion), and analysis after in the field (analysis quantitative and qualitative). The research results show that teachers had implemented the learning thematic on early class (planning, implementation, and evaluation). The result of the implementation of thematic learning consists of 4 aspects, namely planning, implementation, evaluation, and obstacles, obtained 63.54% percentage and entered in the good category. Those means that teachers had implemented thematic learning but not yet optimal. Obstacles that experienced teachers the difficulty in combined between subjects either in planned or presentation weighted. In general, teachers have implemented thematic learning on early class with good. Teachers should more attention to the aspects in thematic learning that the implementation thematic learning more optimal according to the standard of the process and assessment standards prevailing.